2021
DOI: 10.1098/rspb.2021.1287
|View full text |Cite
|
Sign up to set email alerts
|

Pollinators and plant nurseries: how irrigation and pesticide treatment of native ornamental plants impact solitary bees

Abstract: A key conservation goal in agroecosystems is to understand how management practices may affect beneficial species, such as pollinators. Currently, broad gaps exist in our knowledge as to how horticultural management practices, such as irrigation level, might influence bee reproduction, particularly for solitary bees. Despite the extensive use of ornamental plants by bees, especially little is known about how irrigation level may interact with insecticides, like water-soluble neonicotinoids, to influence floral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Installing bee hotels is a popular way of managing leafcutter bees 20 . Yet, recent meticulous field and controlled experiments have documented suboptimal propagation of the brood in bee hotels 16 , 22 . Studies have related this to an increasing parasitism rate in bee hotels 16 , 56 and poor choice of nesting materials 16 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Installing bee hotels is a popular way of managing leafcutter bees 20 . Yet, recent meticulous field and controlled experiments have documented suboptimal propagation of the brood in bee hotels 16 , 22 . Studies have related this to an increasing parasitism rate in bee hotels 16 , 56 and poor choice of nesting materials 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, recent meticulous field and controlled experiments have documented suboptimal propagation of the brood in bee hotels 16 , 22 . Studies have related this to an increasing parasitism rate in bee hotels 16 , 56 and poor choice of nesting materials 16 . A recent study found 75% brood loss (N = 40 brood cells) to parasitism for Megachile lanata in the bee hotels in Bangalore 56 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations